2016
DOI: 10.1104/pp.16.01378
|View full text |Cite
|
Sign up to set email alerts
|

The α-Terpineol to 1,8-Cineole Cyclization Reaction of Tobacco Terpene Synthases

Abstract: Flowers of Nicotiana species emit a characteristic blend including the cineole cassette monoterpenes. This set of terpenes is synthesized by multiproduct enzymes, with either 1,8-cineole or a-terpineol contributing most to the volatile spectrum, thus referring to cineole or terpineol synthase, respectively. To understand the molecular and structural requirements of the enzymes that favor the biochemical formation of a-terpineol and 1,8-cineole, site-directed mutagenesis, in silico modeling, and semiempiric cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…It has been demonstrated that other plant CinSs also accumulate alternative products at significant amounts when expressed in the monoterpenoid production platform. For example, CinS from A. thaliana produces only 42 % cineole with α‐terpineol (19 %), β‐myrcene (16 %), and sabinene (14 %) making up the majority of the rest of the product profile . The question arises, how is bCinS able to tightly control the carbocation intermediates without leakage to other products and/or premature quenching?…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that other plant CinSs also accumulate alternative products at significant amounts when expressed in the monoterpenoid production platform. For example, CinS from A. thaliana produces only 42 % cineole with α‐terpineol (19 %), β‐myrcene (16 %), and sabinene (14 %) making up the majority of the rest of the product profile . The question arises, how is bCinS able to tightly control the carbocation intermediates without leakage to other products and/or premature quenching?…”
Section: Resultsmentioning
confidence: 99%
“…Protonation of the other carbon of the double bond is highly unfavourable, as this would lead to a secondary, rather than tertiary, carbocation, and in our model calculations this spontaneously rearranges to the tertiary cation. The proton acceptor for the final step is unknown, and there is no obvious proton relay network present like the one proposed for CinS from Nicotiana forgetiana , where the hydroxy group of Tyr496 or Thr278 could act as proton acceptor for deprotonation of ( R )‐(+)‐α‐terpineol or ( S )‐(−)‐α‐terpineol, respectively . The most likely candidate for proton abstraction in bCinS is Asn305, due to its close proximity to C7 and strong interaction with the water molecule during simulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GPP and FPP serve as substrates for terpene synthases (TPSs) for synthesizing mono- and sesqui-terpenes, respectively ( Yahyaa et al, 2015 ; Despinasse et al, 2017 ), during which the synthesis of monoterpenes is initiated by GPP dephosphorylation and ionization to geranyl carbocation, while the synthesis of sesquiterpene starts with FPP ionization to a farnesyl cation ( Degenhardt et al, 2009 ; Huang et al, 2010 ). This is then followed by a series of complex chemical mechanisms involving isomerizations, cyclizations, and rearrangements catalyzed by TPSs, which finally generate structurally diverse terpenoids ( Keszei et al, 2010 ; Koo et al, 2016 ; Piechulla et al, 2016 ) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%